Religion and the Human Rights Idea - Johnson, James Turner (Journal of religious ethics, 2018)
Three recent books focus, in different ways, on the idea of human rights and its relation to religion and religious ethics. All three books discussed here address criticisms of the human rights idea and seek to establish the relationship of religion and human rights with regard to the field of policy. The present discussion begins with an overview that places these three books in the larger context of the development of the human rights idea and its historical relationship with religion. It then turns to Little's book, next to the collection of essays edited by Twiss, Simion, and Petersen, which is described internally as a Festschrift for Little, and then to Hogan's book, and in the final section it explores comparisons among the books.